(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
F. Scott Fitzgerald is the most representative writer ofthe jazz age. Glenway Wescott regards Fitzgerald as “a kind of king of ourAmerican youth.” (323) His fiction presents the rootless, directionless andvisionless youth of America of the 1920’s. He revived The Romantic Egoist in1919 for the third time and he titled it This Side of Paradise. This novelexamines the lives and morality of the youth of the jazz age. This Side ofParadise was published in 1920, and in the novel the protagonist, Amory Blaine,came to be read as a person who did not have clear vision and direction. Thenovel explains how Amory goes through different situations, emotional andspiritual circumstances, and how he finally realiz es his true self, and withthis self realization he rediscovers a new Amory within himself.